Preparation and Purification of natural uranium metal by Iodine method. (Baghdad Science Journal, 2008)
In this work ,glass-metal apparatus was designed and manufactured which used for preparing ahigh purity uranium. The reaction is simply take place between iodine vapour and uranium metal at 500C in closed system to form uranium tetra iodide which is decomposed on hot wire at high temperature around 1100C. Also another apparatus was made from Glass and used for preparing ahigh purity of UI4 more than 99.9% purity.